The Myth of Religious Violence: Secular Ideology and the Roots of Modern Conflict - O'Neill, Kevin Lewis (A journal of church and state, 2010)
As the world approaches the tenth anniversary of 9/11 (September 11, 2001), there is a need for pause about the kind and quality of scholarship that has emerged from not simply the events of that day but also the subsequent and so-called Global War on Terror. Much of the scholarship over the last decade has been timely. Much more of it has been alarmist. Written in the style of an intervention, with a robust appreciation for the power of myth on human action and comprehension, William Cavanaugh's The Myth of Religious Violence represents a long awaited voice of reason. Cavanaugh's book centers on the tendency for scholars to understand religion as violent—as promoting violence, as having the means to incite violence, as being comprised of violent characters.